2021
DOI: 10.1186/s12245-021-00336-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a telephone follow-up call for older patients, discharged home from the emergency department on health-related outcomes: a systematic review of controlled studies

Abstract: Background Older patients discharged from the emergency department (ED) are at increased risk for adverse outcomes. Transitional care programs offer close surveillance after discharge, but are costly. Telephone follow-up (TFU) may be a low-cost and feasible alternative for transitional care programs, but its effects on health-related outcomes are not clear. Aim We systematically reviewed the literature to evaluate the effects of TFU by health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Characteristics of the 13 systematic reviews are shown in Table S1. 40,[46][47][48][49][50][51][52][53][54][55][56][57] Of the 17 individual studies, all were published between 1996 and 2018. Among the 17 studies, eight were randomized controlled trials (RCTs), [58][59][60][61][62][63][64][65] three were pre/post studies, 66-68 two were case-control studies, 69,70 and two were nonrandomized clinical trials.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Characteristics of the 13 systematic reviews are shown in Table S1. 40,[46][47][48][49][50][51][52][53][54][55][56][57] Of the 17 individual studies, all were published between 1996 and 2018. Among the 17 studies, eight were randomized controlled trials (RCTs), [58][59][60][61][62][63][64][65] three were pre/post studies, 66-68 two were case-control studies, 69,70 and two were nonrandomized clinical trials.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Through the literature review, 209 systematic reviews were identified, among which 18 were related to pharmacists' involvement in the transition of care. 8 , 9 , 10 , 11 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Three additional articles were identified through screening references included in the identified systematic reviews. 7 , 43 , 44 The main outcome measures in the identified articles were 30-day readmissions, emergency department visits and length of stay.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of this large study, a previous RCT, and a systematic review, we advise not to introduce telephone follow‐up to reduce unplanned hospital admissions and ED return visits in older patients. 4 , 21 , 27 Future studies could evaluate the effects of this intervention on other health‐related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 25 However, up to now only a few studies examined the feasibility and effectiveness of telephone follow‐up for older patients after discharge from the ED. 4 , 18 , 20 , 21 , 26 , 27 , 28 A recent systematic review on this topic could not demonstrate a benefit of the intervention, but only two high‐quality studies met eligibility criteria for this review. 4 , 21 , 27 Only one large randomized controlled trial (RCT) assessed the effect of telephone follow‐up for older patients on hospitalization and ED return visits within 30 days after ED discharge, reporting no benefit of the intervention.…”
Section: Introductionmentioning
confidence: 99%